Genome-wide association mapping identifies novel SNPs for root nodulation and agronomic traits in chickpea - Chandana, B. S.; Mahto, Rohit Kumar; Singh, Rajesh Kumar; Bhandari, Aditi; Tandon, Gitanjali; Singh, K. K.; Kushwah, Sunita; Lavanya, Gera Roopa; Iquebal, Mir Asif; Jain, Neelu; Kudapa, Himabindu; Upadhyaya, H. D.; et al. (Frontiers in Plant Science, 2024)
Introduction The chickpea (Cicer arietinum L.) is well-known for having climate resilience and atmospheric nitrogen fixation ability. Global demand for nitrogenous fertilizer is predicted to increase by 1.4% annually, and the loss of billions of dollars in farm profit has drawn attention to the need for alternative sources of nitrogen. The ability of chickpea to obtain sufficient nitrogen via its symbiotic relationship with Mesorhizobium ciceri is of critical importance in determining the growth and production of chickpea. Methods To support findings on nodule formation in chickpea and to map the genomic regions for nodulation, an association panel consisting of 271 genotypes, selected from the global chickpea germplasm including four checks at four locations, was evaluated, and data were recorded for nodulation and 12 yield-related traits. A genome-wide association study (GWAS) was conducted using phenotypic data and genotypic data was extracted from whole-genome resequencing data of chickpea by creating a hap map file consisting of 602,344 single-nucleotide polymorphisms (SNPs) in the working set with best-fit models of association mapping. Results and Discussion The GWAS panel was found to be structured with sufficient diversity among the genotypes. Linkage disequilibrium (LD) analysis showed an LD decay value of 37.3 MB, indicating that SNPs within this distance behave as inheritance blocks. A total of 450 and 632 stringent marker–trait associations (MTAs) were identified from the BLINK and FarmCPU models, respectively, for all the traits under study. The 75 novel MTAs identified for nodulation traits were found to be stable. SNP annotations of associated markers were found to be related to various genes including a few auxins encoding as well as nod factor transporter genes. The identified significant MTAs, candidate genes, and associated markers have the potential for use in marker-assisted selection for developing high-nodulation cultivars after validation in the breeding populations.